Lexico-Semantic and Grammatical Peculiarities of Comparisons in the Novel «Solo for Solomia» by V. Lys (Linguostylistic Studies, 2018)
Comparisons, like metaphors and metonyms in the artistic text, add expressiveness and vividness to portraying people, their feelings and the surrounding world. It is one of the most important stylistic tropes, and Volodymyr Lys actively uses this classical figurative language device. It is the comparison that helps the writer to create a specific language picture of the world which represents his idiolect. It is worth mentioning that the creativity of V. Lys, in general, manifests his tendency to create complex artistic images using associations. The majority of the comparative structures are anthropocentric by their nature, that is, in the focus is a personality with the individual distinguishing features, own inner world, communication specifics, relations with nature and surrounding realities. Volodymyr Lys, as a gifted master of a word, creates comparative images on the basis of contrast and does it in his own original way. Most of the comparisons are structures created on a national or traditional basis. Despite this, such comparative constructions in the novel of V. Lys sound in a new way, revealing unique multi-faceted world of the epoch. With their help, the author transmits the entire palette of the relationships between people, their tastes, preferences, attitudes to the world around them, the realities, the new things that appeared in their lives. The central images in V.Lys’ works are the Polishuks and their everyday life. Creating comparisons, the author makes use of the local transformed phraseologisms. However, they are transformed so masterfully that, without losing their essence, they sound in a new way, express the individual speech of the characters, depict their appearance and describe the situation. As to the grammatical features of the comparisons in the prose of V. Lys, both simple and complex structures are masterfully woven into the body of the text, but complex and scattered structures prevail and are of special interest for researchers. Due to their specific structure, they can convey complex feelings, emotional states and attitudes to certain realities of life.
Keywords: artistic image; vocabulary; comparison; comparative structure